Workplace Heterogeneity and the Returns to Versatility - Damir Stijepic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In the present paper, I develop an on-the-job search model in which workers face both frictional and structural impediments to sorting. There are two key model predictions. First, versatility enhances the worker's ability to sort into the most productive firms since a mismatch between the job requirements and the worker's skill set is less likely to occur. Second, the larger the productivity differentials between the firms, the larger the returns to sorting and, hence, versatility. I test the latter hypothesis by exploiting industry variation in sales-per-worker dispersion across employers in the United States in 2007. An increase in the sales-per-worker standard deviation by ten log-points is, indeed, estimated to raise the above-median versatile worker's relative wage by 11 to 21 log-points. I also provide supportive evidence from Germany.
Keywords: I26; J31; J24; 330